Enhancing Patient Outcomes through Collaborative Practice between Nurses and Patient Care Technicians - Alfahmi, Ansam Homood; Alharbi, Raneem Fahad; Alsallah, Nada Nasser Mohammed; Almalki, Ahlam Mohammed; Shesha, Raneem Abdullah; Jeddawi, Fawzia Mohammed; Almalki, Asma Abid; Alaki, Bayan Othman Ali; Alharbi, Abdulatef Dakhil Aid (Journal of Posthumanism, 2025)
In the landscape of modern healthcare, the collaborative partnership between Registered Nurses (RNs) and Patient Care Technicians (PCTs) represents a cornerstone of effective, patient-centered care. This research paper explores the dynamics of this critical dyad, examining how structured collaboration, clear role delineation, and effective communication directly contribute to improved patient outcomes, including enhanced safety, greater patient satisfaction, and a higher overall quality of care. This paper analyzes the distinct yet complementary scopes of practice for RNs and PCTs, governed by the foundational principles of delegation as outlined by the American Nurses Association (ANA). It establishes the evidentiary link between high-functioning interprofessional teams and measurable improvements in clinical and patient-reported metrics. Furthermore, the paper identifies common systemic, interpersonal, and structural barriers that impede effective teamwork and presents a suite of evidence-based strategies to overcome them, with a significant focus on the TeamSTEPPS® framework. Through an examination of successful collaborative models, this paper synthesizes its findings into actionable recommendations for clinical practice, healthcare policy, and nursing education. The central thesis is that by intentionally cultivating a culture of mutual respect, psychological safety, and shared purpose, healthcare organizations can leverage the full potential of the nurse-PCT team to meet the complex demands of contemporary patient care and achieve the highest standards of safety and quality